2014
DOI: 10.1016/j.nuclphysb.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Lifshitz scaling effects on holographic superconductors

Abstract: Via numerical and analytical methods, the effects of the Lifshitz dynamical exponent z on the holographic superconductor models are studied in some detail, including s-wave and p-wave models. Working in the probe limit, we calculate the condensation and conductivity in both Lifshitz black hole and soliton backgrounds with a general z. For both the s-wave and p-wave models in the black hole backgrounds, as z increases, the phase transition becomes difficult and the conductivity is suppressed. For the Lifshitz s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 71 publications
(160 reference statements)
8
68
0
Order By: Relevance
“…One of these is known as Lifshitz gravity, which can be dual to scale-invariant field theories, not being conformally invariant. In this context, interesting properties are found when the gauge/gravity duality is generalized to nonrelativistic situations [1][2][3][4][5][6][7][8][9][10][11][12][13], with the Lifshitz holographic a e-mail: rbecar@uct.cl b e-mail: pablo.gonzalez@udp.cl c e-mail: yvasquez@userena.cl superconductor being one of the best studied systems. Such theories exhibit the anisotropic scale invariance t → χ z t, x → χ x, with z = 1, where z is the relative scale dimension of time and space.…”
Section: Introductionmentioning
confidence: 99%
“…One of these is known as Lifshitz gravity, which can be dual to scale-invariant field theories, not being conformally invariant. In this context, interesting properties are found when the gauge/gravity duality is generalized to nonrelativistic situations [1][2][3][4][5][6][7][8][9][10][11][12][13], with the Lifshitz holographic a e-mail: rbecar@uct.cl b e-mail: pablo.gonzalez@udp.cl c e-mail: yvasquez@userena.cl superconductor being one of the best studied systems. Such theories exhibit the anisotropic scale invariance t → χ z t, x → χ x, with z = 1, where z is the relative scale dimension of time and space.…”
Section: Introductionmentioning
confidence: 99%
“…It also indicates that condensation versus temperature have a square root behavior near T c , which suggests that the critical exponent is 1/2, as expected from the mean field theory. The Lifshitz scaling and spacetime dimension will not influence the result [19].…”
Section: The D-wave Holographic Superconductor Models With Lif-shmentioning
confidence: 98%
“…It is found that the Lifshitz black hole geometry results in different asymptotic behaviors of temporal and spatial components of gauge fields compared to those in the Schwarzschild-AdS black hole, which brings some new features of holographic superconductor models. More recently, Lu et al discussed the effects of the Lifshitz dynamical exponent z on holographic superconductors and gave some different results from the Schwarzschild-AdS background [19]. To date, there have attracted considerable interest to generalize the holographic superconducting models to nonrelativistic situations [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, thermodynamics of Gauss-Bonnet-dilaton Lifshitz black branes has been discussed in [27]. The idea of holography has been applied for systems with Lifshitz symmetry in different contexts including dilaton gravity from different points of view [28][29][30] and behaviors of some quantities such as viscosity [31,32] and different kinds of conductivity [12,[33][34][35][36][37][38] have been analyzed. The authors of ref.…”
Section: Jhep03(2016)037mentioning
confidence: 99%
“…Employing the gauge/gravity duality the holographic superconductors were explored with z = 2 Lifshitz scaling [35]. The effects of Lifshitz dynamical exponent z on the holographic superconductor models including s-wave and p-wave models have been disclosed both numerically and analytically in [36]. Via holography, superconducting phase transitions of a system dual to Yang-Mills field coupled to an axion as probes of black hole with arbitrary Lifshitz scaling have been studied with p x +ip y condensate [37].…”
Section: Jhep03(2016)037mentioning
confidence: 99%